Effects of game-product congruence on game-players’ brand attitude in mobile games: a review - Toh, Yuan Kai; Hashim, Haslinda; Abdul Aziz, Yuhanis; Ng, Siew Imm (Human Resource Management Academic Research Society, 2019)
Advertising is a marketing communication tool used by marketers to convey their brand messages to targeted consumers. Over the years, the effectiveness of traditional advertising has greatly diminished due to the clutter of advertisements that impede consumers’ ability to process and retain advertising messages. As such, marketers are always seeking creative advertising strategies such as product placements, to capture consumers’ attention and break away from the clutter of advertising messages. In the era of digital technology, product placements are no longer restricted to traditional entertainment medium such as reality TV shows or movies. Thanks to innovations in smartphone and digital gaming technologies, the use of mobile games as an advertising platform has also become a reality in recent years. As a relatively new phenomenon, there are ample research opportunities on product and brand placements in mobile games since many areas have not yet been fully explored. Furthermore, several past studies examining the influence of different product placement strategies on advertising effectiveness have reported mixed findings thereby suggesting the need for further research. The findings of these studies are expected to provide valuable insights to the academic community as well as marketing practitioners considering mobile games as an alternative medium to advertise and promote their brands.